The Influence of Benzamidine Derivatives on Human Platelet Function - Glusa, Erika; Barthel, Wolfgang; Markwardt, Fritz (Thrombosis and Haemostasis, 1974)
The influence of derivatives of benzamidine, benzylamine and phenylguanidine on platelet function was investigated in vitro. Among the compounds tested 4-nitro-benzoic acid 4’-amidinoanilide, 4-aminobenzoic acid 4’-amidinoanilide, 4-amidino-benzoic acid anilide and 4-amidinobenzoic acid 3’,4’-dimethoxyanilide were found to be potent inhibitors of platelet aggregation induced by ADP, collagen and thrombin. Other platelet functions, such as the thrombin-induced amine liberation, serotonin and adenosine uptake, retraction and phosphodiesterase activity, were not influenced. The action of the benzamidine derivatives, known to be thrombin inhibitors, is not caused by an inhibition of the clotting enzyme, but it seems to be mainly due to the prevention of the ADP effect on platelets.